Taste Quality and Intensity of 100 Stimuli as Reported by Rats: The Taste–Location Association Task - Gautam, Shree Hari; Rebello, Michelle R.; Verhagen, Justus V. (Frontiers in Behavioral Neuroscience, 2012)
The interpretation of neural activity related to sensory stimulation requires an understanding of the subject's perception of the stimulation. Previous methods used to evaluate the perception of chemosensory stimuli by rodents have distinct limitations. We developed a novel behavioral paradigm, the taste-location association task, to complement these methods. First we tested if rats are able to learn associations between five basic taste stimuli and their spatial locations. This spatial task was based on 4 prototypical tastants and water. All four rats trained to perform the task reached levels of performance well above chance. Control trials demonstrated that the rats used only taste cues. Further, the learned stimulus set was resistant to interference, allowing for generalization experiments performed subsequently. We tested the rats' gustatory generalizations of 100 tastants to the five trained stimuli, both regarding their taste qualities as well as intensity ratings. The taste profiles generated by these experiments contribute to the understanding of how perception of the specific taste stimuli relate to the perception of the five basic taste qualities in intact behaving rats. In this large taste space we found that intensity plays a major role. Furthermore, umami stimuli were not reported as being similar to other basic tastants. Our new paradigm enables neurophysiological studies of taste-based learning and memory in awake, freely moving animals.